Chad : Staff Monitored Program. (IMF Staff Country Reports; Country Report ;, 2009)
The Chadian authorities have requested a staff-monitored program (SMP) during April-October 2009 to demonstrate improvements in fiscal policy and public financial management. The objective is to re-establish their economic management and reform credentials with international development partners, with a view to increasing donor support for their poverty reduction strategy. The cornerstone of this SMP is the implementation of a revised budget for 2009 based on a realistic oil price assumption. The SMP also aims to signal a clear return to an orderly budgetary framework by curtailing the use of exceptional budgetary procedures.